Genetic Diversity Among Some Aspergillus flavus Isolates by Using Inter simple sequence repeats (ISSR) - M. Abdulateef, Safa; H. Aljubori, Mona; J. Abdulbaqi, Neamat (Iraqi Journal of Science, 2023)
Aspergillus flavus isolates which are considered on conidial shape through microscopic examination and mycelial colour through cultural properties . Primary screening for the ability of A. flavus isolates for aflatoxin production was determined using A.flavus parasiticus agar medium (AFPA) as well , 7 isolates from 11 isolates give a positive result by the presence of bright yellow-orange pigments indicated the presence of aflatoxins. Molecular genetics techniques using DNA polymorphism have been increasingly used to characterize and identify genetic diversity and relationships among eleven A. flavus isolated from different source using the ISSR(inter simple sequence repeats) technique. Three universal primers designed at University of British Columbia (UBC 809 , UBC 810, UBC 811) were produced (18) main bands of these bands, 53 bands were polymorphic. The size of the amplified bands ranged between 100-1,500 bp. The genetic polymorphism value of each primer was ranged between 16.98-74.4%. In terms of unique banding patterns, determine the finger print for one isolate the most characteristic banding pattern was for the isolate number 5 with primer UBS primer No.809. Genetic distances ranged from 0.12599 to 0.93644 among A.flavus isolates. Cluster analyses were performed to construct a dendrogram placed most of the A. flavus was isolated from the different source at the same main group.